1959
DOI: 10.1055/s-0028-1101626
|View full text |Cite
|
Sign up to set email alerts
|

ALTOSID, EIN HERZAKTIVES GLYKOSID AUSURGINEA ALTISSIMABAKER1

Abstract: h t i , A. von W a r t b u r g U. J. R e n z Unter dem Begriff "Herzaktive Glykoside" versteht der Chemiker eine Gruppe von Naturstoffen, die sich durch eine starke und spezifische Wirkung auf die Herzmuskulatur von Mensch und Tier auszeichnen. Diese Glykoside finden sich in recht verschiedenen Pflanzenfamilien, wobei die Afiocynaceen und die Asclepiadaceen besonders reich vertreten sind.Die ersten chemischen Arbeiten über herzaktive Glykoside stammen aus dem 19. Jahrhundertabgesehen von einigen Versuchen im 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Urgineanin B ( 2 ), [α] 21 D +18 ( c 0.12, MeOH), was also isolated as a light yellow oil; its composition was established as C 19 H 20 O 7 by positive ion HRESIMS. Comparison of 1 H and 13 C NMR spectroscopic data of 2 with those of 1 (Table 1) indicated that both compounds had the same skeleton and substitution pattern, and differed only in that 2 had a hydroxy group in place of one of the O -methyl groups of 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Urgineanin B ( 2 ), [α] 21 D +18 ( c 0.12, MeOH), was also isolated as a light yellow oil; its composition was established as C 19 H 20 O 7 by positive ion HRESIMS. Comparison of 1 H and 13 C NMR spectroscopic data of 2 with those of 1 (Table 1) indicated that both compounds had the same skeleton and substitution pattern, and differed only in that 2 had a hydroxy group in place of one of the O -methyl groups of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Urgineanin C ( 3 ), [α] 21 D +9, was identified as the homoisoflavonoid (3 S )-5,6,7-trimethoxy-3-(4-methoxybenzyl)chroman-4-one by comparison of its experimental and reported physical and spectroscopic data. 14,15 Based on the positive π→π* Cotton effect (Δε = 5.6) at 286 nm and a negative n→ π * Cotton effect (Δε = −2.8) at 251 nm, the absolute configuration of C-3 was assigned as S , enantiomeric with the reported compound.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations